2010
DOI: 10.3113/fai.2010.0277
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Lesions of the Talus Treated With Fresh Talar Allografts

Abstract: Based on these results, we conclude that this is a reasonable procedure for younger adult patients with focal osteochondral talar defects that cannot be corrected with curettage and microfracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 28 publications
4
60
0
Order By: Relevance
“…Second, owing to the uncommon nature of this condition, we had a limited sample size. Third, the mean length of followup for this study was 3.3 years, which is shorter than in some previous studies [18,20,24,38,45] evaluating fresh osteochondral allograft transplantation for the management of talar OCDs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Second, owing to the uncommon nature of this condition, we had a limited sample size. Third, the mean length of followup for this study was 3.3 years, which is shorter than in some previous studies [18,20,24,38,45] evaluating fresh osteochondral allograft transplantation for the management of talar OCDs.…”
Section: Discussionmentioning
confidence: 86%
“…First, as with other allograft studies [18,20,24,27,30,32,37,38,45], we used a prospective cohort design with no control group. A prospective control group was not feasible, as we believe that other treatment options, including total ankle arthroplasty or arthrodesis, would greatly limit function and mobility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen et al (21) also present autologous chondrocyte implantation as a promising technique for chondral lesions of the knee and of the talus. Other authors still advocate the use of mosaicplasty (22) or fresh talus allograft (23) . Gras et al (24) propose the use of navigation in association with arthroscopy aiming to improve the accuracy of the retrograde perforation of cystic osteochondral lesions.…”
Section: Treatment Of Osteochondral Lesions Of the Talus By Means Of mentioning
confidence: 99%
“…There are several papers about osteochondral allograft transplantation for the treatment of OLT, and most are small prospective and retrospective case series [74][75][76][77][78][79][80]. El-Rashidy et al [79] performed one of the largest studies in patients who received small cylindrical allografts and reported good or excellent outcomes in 28 of 38 patients at mean 37.7 months of follow-up.…”
Section: Osteochondral Allograft Transplantationmentioning
confidence: 99%